2000
DOI: 10.1046/j.1365-3156.2000.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of human hookworm infections in the southern region of Mali

Abstract: Two surveys of hookworm (Necator americanus) infections, conducted three years apart (December 1994 and January 1998) in a village in the Sikasso region of Mali, revealed that overall prevalence of infection was 68.7% and 53%, respectively. In both years there was a highly significant difference between the sexes in the prevalence and abundance of infection, with male subjects carrying heavier infections than females. Both prevalence and abundance of infection increased with age, although in 1998 there was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
4
41
4
Order By: Relevance
“…However, different results have been observed by others worldwide. In China and Southeast Asia, the highest prevalence was observed in the middle-aged or even in individuals over 60 years old 8,10,20,30 . Such age profiles of hookworms contrast to the rapid increase in prevalence of Ascaris lumbricoides and Trichuris trichiura, for which the prevalence reaches a maximum in 5-to 10-year-olds and remains relatively stable throughout adulthood 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, different results have been observed by others worldwide. In China and Southeast Asia, the highest prevalence was observed in the middle-aged or even in individuals over 60 years old 8,10,20,30 . Such age profiles of hookworms contrast to the rapid increase in prevalence of Ascaris lumbricoides and Trichuris trichiura, for which the prevalence reaches a maximum in 5-to 10-year-olds and remains relatively stable throughout adulthood 12 .…”
Section: Discussionmentioning
confidence: 99%
“…19,25 Furthermore, we did not screen for hookworm infections or schistosomiasis, which can influence hematological indices and are prevalent in some regions of southern Mali. 26,27 In summary, our study highlights the complexity of establishing reference intervals for hematological indices in African children, and using these indices to estimate anemia prevalence and parasite density. In our cohort of Malian children aged 3-12 years, RBC and WBC indices changed significantly not only between age groups, but also within each age group during a 7-month transmission season.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier epidemiological studies have also reported the predominance of hookworm infections in some communities in Ghana 38,39 , Mali 40 , Kenya 41 and Nigeria 42 . As reported by Hotez et al, 4 , hookworm infection is still a significant public health problem in Sub-Saharan Africa.…”
Section: Fig 3: Pictures Of Hookworm Larvae Recovered From the Stoolmentioning
confidence: 87%